The Control of Bleeding in Splenectomized Animals by Ellagic Acid - Agostino, D; Cliffton, E. E (Thrombosis and Haemostasis, 1967)
1. Blood loss after splenectomy was reduced significantly by i. v. injection of ellagic acid.2. The duration of bleeding was also shortened significantly.3. There were no obvious toxic manifestations and no evidence of thrombosis.